2017
DOI: 10.1038/ng.3858
|View full text |Cite
|
Sign up to set email alerts
|

DUX-family transcription factors regulate zygotic genome activation in placental mammals

Abstract: In metazoan embryos, transcription is mostly silent for a few cell divisions, until release of a first major wave of embryonic transcripts by so-called zygotic genome activation (ZGA) 1. Maternally provided ZGA-triggering factors have been identified in Drosophila melanogaster and Danio rerio 2,3, but their mammalian homologues are still undefined. Here, we reveal that the DUX family of transcription factors 4,5 is essential to this process in human and mouse. First, human DUX4 and murine Dux are both expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

28
562
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 493 publications
(626 citation statements)
references
References 43 publications
(62 reference statements)
28
562
1
1
Order By: Relevance
“…Maternal deletion of Yap1 results in failure to form a blastocyst, downregulation of ~3000 ZGA transcripts, and upregulation of ~1300 otherwise degraded transcripts. Other activators include the Zscan transcription factors, which are expressed specifically in the 2 cell embryo (Falco et al, 2007; Ko, 2016), NFYa, which likely directly regulates some genes activated in the 2-cell embryo (Lu et al, 2016), and the DUX (mouse) and DUX4 (human) homeobox transcription factors (De Iaco et al, 2017; Hendrickson et al, 2017; Whiddon et al, 2017). Intriguingly, DUX4 directly induces several hundred early human ZGA target genes, including HERVL retrotransposons, at the 4–8 cell stage.…”
Section: Transcriptional Activation By Activatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maternal deletion of Yap1 results in failure to form a blastocyst, downregulation of ~3000 ZGA transcripts, and upregulation of ~1300 otherwise degraded transcripts. Other activators include the Zscan transcription factors, which are expressed specifically in the 2 cell embryo (Falco et al, 2007; Ko, 2016), NFYa, which likely directly regulates some genes activated in the 2-cell embryo (Lu et al, 2016), and the DUX (mouse) and DUX4 (human) homeobox transcription factors (De Iaco et al, 2017; Hendrickson et al, 2017; Whiddon et al, 2017). Intriguingly, DUX4 directly induces several hundred early human ZGA target genes, including HERVL retrotransposons, at the 4–8 cell stage.…”
Section: Transcriptional Activation By Activatorsmentioning
confidence: 99%
“…Intriguingly, DUX4 directly induces several hundred early human ZGA target genes, including HERVL retrotransposons, at the 4–8 cell stage. DUX4/DUX family genes are found in telomeric and pericentromeric regions as multicopy loci and appear specific to placental mammals, suggesting that DUX transcription factors could be critical drivers of embryonic genome activation in the mammalian lineage (De Iaco et al, 2017; Hendrickson et al, 2017; Whiddon et al, 2017). DUX itself is zygotically expressed by unknown mechanisms, indicating that key maternally deposited regulators of human and mouse ZGA remain to be identified.…”
Section: Transcriptional Activation By Activatorsmentioning
confidence: 99%
“…For example, totipotent 2-cell (2C) mouse embryos are characterized by massive transcriptional activation of MERV-L loci [46,48]. Notably, a trio of recent studies showed that MERV-L activation is driven by the host transcription factor mouse Dux [5153]. Past the 2C stage, mouse ESCs exhibit markedly reduced MERV-L transcription along with a subsequent peak in ERVK and MaLR expression [54] driven by binding of pluripotency-associated TFs like Nanog and Oct4 [54].…”
Section: Erv Choreography In Early Embryonic Developmentmentioning
confidence: 99%
“…Deep RNA sequencing has revealed that the expression of individual HERV families is precisely regulated during early embryonic development [35,51,56]. Notably, DUX4, a human homolog of mouse Dux, appears to be a crucial regulator of HERV-L LTR transcription in 4-cell-stage embryos [51,53]. Hundreds of ape-specific HERV-H elements are also transcriptionally activated by pluripotency TFs in human ESCs [5760].…”
Section: Erv Choreography In Early Embryonic Developmentmentioning
confidence: 99%
“…Many of the identified genes are normally restricted to the 2-cell (2C) stage of embryogenesis, when zygotic genome activation (ZGA) is initiated in mice (Macfarlan et al, 2012). The 2C genetic program is largely controlled by a single transcription factor, Dux (De Iaco et al, 2017; Hendrickson et al, 2017). LINE1 KD in mESCs reduced the repressive mark H3K9me2 at the Dux locus and activated Dux target gene transcription.…”
mentioning
confidence: 99%